The Critical Role of Arbuscular Mycorrhizal Fungi to Improve Drought Tolerance and Nitrogen Use Efficiency in Crops - Tang, Haiying; Hassan, Muhammad Umair; Feng, Liang; Nawaz, Muhammad; Shah, Adnan Noor; Qari, Sameer H.; Liu, Ying; Miao, Jianqun (Frontiers in Plant Science, 2022)
Drought stress (DS) is a serious abiotic stress and a major concern across the globe as its intensity is continuously soaring up. Therefore, it is direly needed to develop new management strategies to mitigate adverse effect of DS for ensuring better crop productivity and food security. The use of arbuscular mycorrhizal fungi (AMF) has emerged as an important approach in recent years to improve the crop productivity under DS conditions. AMF establish relationship with 80% of land plants and it induces pronounced impacts on pant growth and provides protection to plants from abiotic stress. Drought stress significantly reduce the plant growth and development by inducing oxidative stress, disturbing membranes integrity, plant water relations, nutrient uptake, photosynthetic activity, photosynthetic apparatus, and anti-oxidant activities. However, AMF can significantly improve the plant tolerance against DS. AMF maintains membrane integrity, improves plant water contents, nutrient and water uptake and water use efficiency (WUE) therefore, improve the plant growth under DS. Moreover, AMF also protects the photosynthetic apparatus from drought induced oxidative stress and improve photosynthetic efficiency, osmolytes, phenols and hormones accumulation and reduce the accumulation of reactive oxygen species (ROS) by increasing anti-oxidant activities and genes expression which provide the tolerance to plants against DS. Therefore, it is imperative to understand about the role of AMF in plants grown under DS. This review presented the different functions of AMF in different responses of plants under DS. We have provided a detailed picture on the different mechanisms mediated by AMF to induce drought tolerance in plants. Moreover, we also identified the potential research gaps that must be fulfilled for promising future of AMF. Lastly, nitrogen (N) is an important nutrient needed for plant growth and development, however, efficiency of applied N fertilizers is quite low. Therefore, we also present the information how AMF improves N uptake and nitrogen use efficiency (NUE) in plants.